UNDERSTANDING HOMEOPATHY: A REVIEW OF ITS PRINCIPLES, PRACTICES, AND INTEGRATION INTO MODERN MEDICINE - Shrivastava, Rishi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Homeopathy, a system of alternative medicine founded by Samuel Hahnemann in the late 18th century, is based on principles such as the Law of Similars, potentization, and individualized treatment. Despite its controversial scientific standing, homeopathy continues to influence modern healthcare, particularly in the context of holistic and integrative medicine. This review examines the core principles of homeopathy, its doctrinal foundations, and its growing role in contemporary healthcare. The article also explores the challenges and opportunities associated with integrating homeopathy into mainstream medicine, highlighting the need for further research and dialogue. Examples from current medical practices, such as personalized medicine, probiotics, and holistic approaches, are discussed to illustrate the parallels and potential synergies between homeopathy and modern medicine.